2018
DOI: 10.1101/334136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Community Structure and Diversity of Shrimp Paste at Different Fermentation Stages

Abstract: 9High-throughput sequencing was used to reveal the highly diverse bacterial 10 populations in shrimp paste at different fermentation stages. We studied three stages of 11 fermentation and obtained 448,916 reads. Using this approach, we revealed the presence 12 of 30 phyla, 55 classes, 86 orders, 206 families and 695 genera of bacteria in the shrimp 13 paste. Shrimp paste in fermentation metaphase had a more diverse microbiota than that in 14 fermentation prophase and fermentation anaphase. Diversity appeared g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The dominance of Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes in shrimp microbiome in this study showed similarity with the previous studies (Rungrassamee et al, 2013;Tzeng et al, 2015;Huang et al, 2016). Interestingly, bacterial communities detected in shrimp paste produced from China were also dominated by the same phyla (Dai et al, 2018). Huang et al (2016) and Zheng et al (2017) reported that the bacterial diversity of white shrimp, Litopenaeus vannamei is significantly different in genus level at different life stages but the phylum level was similar even after undergoing food processing.…”
Section: Discussionsupporting
confidence: 87%
“…The dominance of Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes in shrimp microbiome in this study showed similarity with the previous studies (Rungrassamee et al, 2013;Tzeng et al, 2015;Huang et al, 2016). Interestingly, bacterial communities detected in shrimp paste produced from China were also dominated by the same phyla (Dai et al, 2018). Huang et al (2016) and Zheng et al (2017) reported that the bacterial diversity of white shrimp, Litopenaeus vannamei is significantly different in genus level at different life stages but the phylum level was similar even after undergoing food processing.…”
Section: Discussionsupporting
confidence: 87%
“…Within each of fermented shrimp products, there was a correlation between dominant bacterial communities and flavor, safety, and quality (K. H. Kim et al, 2019;Pongsetkul et al, 2017;Tamang, Shin, et al, 2016;Visessanguan & Chaikaew, 2015). For instance, the shrimp paste from the study by Dai et al (2018) was found to contain the genera Psychrobacter and Halomonas which are predominant during different stages of fermentation. The two bacteria grew well in high salt concentrations and were often associated with food spoilage and hygiene issues, respectively (Burch et al, 2013;Møretrø & Langsrud, 2017;G.…”
Section: Microbial Diversity In Fermented Shrimp Productsmentioning
confidence: 99%
“…The two bacteria grew well in high salt concentrations and were often associated with food spoilage and hygiene issues, respectively (Burch et al., 2013; Møretrø & Langsrud, 2017; G. Wu et al., 2015). This was because both Psychrobacter and Halomonas were able to release lipolytic enzymes that facilitate degradation of lipids, resulting in off‐flavor in high‐salt fermentation (Dai et al., 2018; B. M. Kim et al., 2015).…”
Section: Microbiology In Fermented Shellfish Condimentsmentioning
confidence: 99%
See 2 more Smart Citations